The ComSoc guide to passive optical networks : enhancing the last mile access - Weinstein, Stephen B.; Luo, Yuanqiu; Wang, Ting. (Hoboken, NJ : Wiley, 2012)
"The goal of this guidebook is to provide the general readers with a high level overview of the technology and applications behind the Fiber-to-the-Home (FTTH) or Fiber-to-the-Curb (FTTC) family of standards, which has recently attracted considerable amount of interest in the technical community"--
Includes bibliographical references and index.
Keywords: Passive optical networks; TECHNOLOGY & ENGINEERING / Fiber Optics